Dentist Knowledge and Behavior on use of Smart Phones in Clinical Environment and their association with Cross Infections - Khizer Mehmood, Alia Batool, Muhammad Imtiaz, Sharoon Hanook, Muhammad Asif Shahzad, Qasim Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The use of smart phones inside hospitals especially in clinically sensitive areas is a subject of debate because it may improve the quality of healthcare but can also be a vehicle of hospital acquired infections. Aim: To determine dentist’s knowledge and behavior related to the use of smart phones in clinical environment and to determine the presence of microbial growth on these devices. Methods: This is a cross-sectional study in which validated survey tool was used to collect data about knowledge and behavior of 397 dental graduates from 8 dental colleges of Pakistan, regarding their usage of smart phones in clinical environment. Bacterial isolates were collected from the smart phones of 45 participants from Fatima Memorial Dental Hospital, Lahore. Results: The SPTC Scale was used to divide the participants into 3 categories; low, moderate and high users. The behavior related to smart phone usage in clinical environment was significantly different among the participants. Moderate users had significantly higher average behavior score of 3.7 (p-value = 0.034). The growth of pathogenic bacterial flora was greater on high users of smart phones (95%,) whereas those participants who were low users the percentage was 37%. Conclusion: Hospital-acquired infections (HAIs) are increasing significantly in number of patients and these can be prevented by adhering to proper hand hygiene practices and if hand hygiene is improved the amount of bacterial load will be less and disinfection of smart phone devices will not be required. Keywords: Smartphone; Dental Clinics; Smartphone time consumption scale (SPTC); cross infection; Hand washing